2015
DOI: 10.1016/j.healthplace.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Blue space geographies: Enabling health in place

Abstract: a b s t r a c tDrawing from research on therapeutic landscapes and relationships between environment, health and wellbeing, we propose the idea of 'healthy blue space' as an important new development Complementing research on healthy green space, blue space is defined as; 'health-enabling places and spaces, where water is at the centre of a range of environments with identifiable potential for the promotion of human wellbeing'. Using theoretical ideas from emotional and relational geographies and critical unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 112 publications
6
155
0
2
Order By: Relevance
“…There is considerable scope to develop future work through a range of swimming spaces (including indoors and private settings) and swimming bodies (Foley and Kistemann, 2015). In further exploring relationships between blue space, embodiment and physical heath, numerous recreational health pursuits -floating, snorkelling, diving, kayaking, surfing, rowing and sailing e increasingly use innovative methodologies (Go-pro cameras, waterproof sound recorders) to capture more-than-emotional geographies in place and uncover in-situ experiential narratives (Merchant, 2011;Bell et al, 2015;Brown and Humberstone, 2015).…”
Section: Conclusion: Swimming Bodies Emotions and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable scope to develop future work through a range of swimming spaces (including indoors and private settings) and swimming bodies (Foley and Kistemann, 2015). In further exploring relationships between blue space, embodiment and physical heath, numerous recreational health pursuits -floating, snorkelling, diving, kayaking, surfing, rowing and sailing e increasingly use innovative methodologies (Go-pro cameras, waterproof sound recorders) to capture more-than-emotional geographies in place and uncover in-situ experiential narratives (Merchant, 2011;Bell et al, 2015;Brown and Humberstone, 2015).…”
Section: Conclusion: Swimming Bodies Emotions and Practicesmentioning
confidence: 99%
“…In all cases, those experiences and practices are shaped by explicit references to emotions and feelings that emerge in place (Edensor, 2010). In the ever-widening range of writing on emotional geographies, health and wellbeing have also become increasingly explicit dimensions (Davidson et al, 2005;Parr and Davidson, 2010), while psychologists have also explored nature-based health (Hartig et al, 2015) How those emotional and healing strands build and come together as a therapeutic accretion through the practice of swimming within 'healthy blue space' is at the heart of this paper (Foley and Kistemann, 2015).…”
mentioning
confidence: 99%
“…The importance of connection with, challenges of and immersion in nature has been highlighted by researchers exploring the impact of both "green space" and especially "blue space" on the health and wellbeing of individuals and communities [29,34,62]. Previous research on interventions carried out in "natural" environments (including surfing) has found positive benefits on participant's social skills, confidence and wellbeing [29,55,63].…”
Section: Surfing As Saviourmentioning
confidence: 99%
“…More recently, there has been a move within literature to refer simply to 'therapeutic spaces,' dropping the 'landscape' aspect of the concept, as a means of beginning to recognise the more-than-terrestrial spaces which can impact on health and wellbeing (Foley and Kistemann 2015) and broaden the ways in which geographers engage with ideas of health and place. Indeed, the wording of 'landscape' in the titling of the concept is perhaps something of a misnomer, often leading to an over-focusing on the physical environment, indeed Gesler (1992) lamented that 'the first reaction one encounters when mentioning therapeutic landscapes is that what is meant is bucolic locales, health spas, and the like ' (p.743).…”
Section: Therapeutic Spacesmentioning
confidence: 99%
“…The non-human presence actively creates and facilitates a therapeutic engagement with place, influencing not only how people experience health and care on the farm, but also how they visualise themselves; a reconfiguring of the relational self, caused by the participants becoming imbricated with non-human actants (Conradson 2005). Similarly to Foley and Kistemann's (2015) discussions of therapeutic blue spaces, the farms have emotional and life course resonances that extend far beyond specific single encounters; an affective journey through and with the therapeutic space that creates a long-lasting therapeutic relation even once the physical site of the therapeutic landscape is left. It is an affect made possible by bringing (or simply embracing the presence of) the non-human into a therapeutic space, and deliberately creating the opportunities for inter-species encounters.…”
Section: Social and Cultural Geography 23mentioning
confidence: 99%